Daya Saing Bawang Merah di Provinsi Maluku dan Upaya Peningkatannya - Agung Budi Santoso; Maryam Nurdin; Ismatul Hidayah (Jurnal Ilmu Pertanian Indonesia, 2020)
Shallot is one of horticultural commodities with a high demand. Majority of shallots in Maluku are bought from Surabaya and Makasar. However, the government continuously does horticultural development in the center of shallot production. The objective of this study was to analize the competitiveness and comparativeness of farming between shallots which are cultivated by local farmer and shallots which are imported. There were three locations of research i.e., Maluku Tenggara, Seram Bagian Barat, and Maluku Tengah. Primary data were collected by quessioner and used purposive sampling method. Primary data were analyzed using policy analysis matrix. The results showed that shallot farming in Maluku has comparative and competitive advantages compared with imported shallots. Agricultural government policy effectively increases local farmer insentive. However, it shows a decreasing trend while increasing productivity of shallot. Shallot farming having production higher than 8 ton/ha need output subsidy to give price guarantee. Effort to increase shallot competitiveness is conducted by increasing productivity and developing a farmer institution to make a sustainable agricultural development. Keywords: shallot, competitiveness, competitive and comparative